2020
DOI: 10.3390/plants9091099
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation of Phenolic and Mineral Composition in Olive Leaves Is Cultivar Dependent

Abstract: In order to investigate the potential of various olive cultivars and leaf sampling times for phytochemical farming practice in Croatia, phenolic and mineral composition was determined in olive leaves of four Croatian cultivars and Italian cultivar Leccino collected at three occasions, in October 2017, January 2018, and March 2018. Istarska bjelica turned out to have the largest phytochemical potential among the investigated cultivars due to steady high oleuropein concentrations found in its leaves. The concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 46 publications
6
35
3
Order By: Relevance
“…Among all of the investigated flavonoids, luteolin-7- O -glucoside was predominant in all plant parts. A strongly positive correlation between this flavonoid and Mn concentration was obtained with r = 0.81 and p = 0.01 ( Table 2 ), which was in agreement with our previously reported results [ 55 ]. The significant increase in the concentration of luteolin-7- O -glucoside in leaves under the enhanced Mn supply ( Figure 1 ) might imply its more specific functional aspect.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Among all of the investigated flavonoids, luteolin-7- O -glucoside was predominant in all plant parts. A strongly positive correlation between this flavonoid and Mn concentration was obtained with r = 0.81 and p = 0.01 ( Table 2 ), which was in agreement with our previously reported results [ 55 ]. The significant increase in the concentration of luteolin-7- O -glucoside in leaves under the enhanced Mn supply ( Figure 1 ) might imply its more specific functional aspect.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the concentration of oleuropein in leaves significantly increased at 24 µM Mn compared to 0.2 µM Mn in nutrient solution that was applied when growing olive plantlets ( Figure 1 ), suggesting a potentially stimulative role of Mn ion on the oleuropein biosynthesis. The initially high oleuropein amount found at 0.2 µM Mn could be ascribed to the type of cultivar since it is known that ‘Istarska bjelica’ is one of the Croatian cultivars with the highest olive leaf oleuropein potential [ 55 ]. In addition, the concentration of oleuropein was the highest under 24 µM Mn treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Olive cultivar, geographical origin, maturity stage, climate, tree/leaf lifetime, as well as sampling/harvest time and storage are typical pre-harvest and post-harvest agronomical and technological factors affecting the phenolic compounds and overall chemical composition of olive leaves [ 42 , 66 ]. In a 2016 study, olive leaves total polyphenols were found to vary from 7.87 to 34.21 mg/g depending on the kind of leaf (fresh, refrigerated, dried, frozen, or lyophilized), cultivar, sampling time, and production area [ 74 ].…”
Section: Varietal and Agronomic Variables Influencing Functional Compounds Contentmentioning
confidence: 99%
“…Olive cultivars may have a different response from biotic or abiotic factors, consequently leading to distinct olive leaves’ phenolic profiles and antioxidative activity [ 24 ]. Oleuropein concentration and antioxidant activity in Drobnica, Leccino, Levantinka, and Oblica leaves increased following exposure to low air temperatures, which may be of crucial interest for designing more efficient and sustainable phytochemical farming strategies [ 66 ]. Leaves from olive trees continuously exposed to environmental stresses such as high temperature and UV radiation have produced phenolic alcohols, secoiridoids, and flavonoids, whose quantitative and qualitative changes depended on cultivar, maturation degree of the leaf, infestation caused by Dacus olea, climate, and geographical origin [ 32 ].…”
Section: Varietal and Agronomic Variables Influencing Functional Compounds Contentmentioning
confidence: 99%
“…HPLC-UV/VIS analysis. Phenols in OL methanolic extracts and freshly prepared OLI were determined by HPLC Ultimate 3000 System with ultraviolet/visible spectrophotometry (UV/VIS) detector (Thermo-Fisher Scientific, Waltham, USA) according to the method of Pasković et al (2020). The analytical column was Lichrospher 100 RP-18 (250 × 4 mm, 5 μm) https://doi.org/10.17221/185/2020-CJFS with pre-column Lichrospher 100 (4 × 4 mm, 5 μm), supplied by Agilent Technologies (Santa Clara, USA).…”
Section: Methodsmentioning
confidence: 99%